Occupational exposure to respirable crystalline silica and lung cancer: a systematic review of cut-off points - Julia Rey-Brandariz; Cristina Martínez; Cristina Candal-Pedreira; Mónica Pérez-Ríos; Leonor Varela-Lema; Alberto Ruano-Ravina (BMC, 2023)
Abstract Background Respirable crystalline silica (RCS) is associated with the development of lung cancer. However, there is uncertainty around the exposure threshold at which exposure to RCS may pose a clear risk for the development of lung cancer. The objective of this study was to review the cut-off points at which the risk of mortality or incidence of lung cancer due to occupational exposure to RCS becomes evident through a systematic review. Methods We conducted a search in PubMed, including cohort and case-control studies which assessed various categories of RCS exposure. A search was also conducted on the webpages of institutional organizations. A qualitative data synthesis was performed. Results Twenty studies were included. Studies that assessed lung cancer mortality and incidence displayed wide variability both in RCS exposure categories and related risks. Although most studies found no significant association for RCS exposure categories, it appears to be a low risk of lung cancer for mean concentrations of less than 0.07mg/m3. Regulatory agencies set annual RCS exposure limits ranging from 0.025mg/m3 through 0.1mg/m3. Conclusions There is a wide degree of heterogeneity in RCS exposure categories, with most studies observing no significant risk of lung cancer for the lowest exposure categories. Cut-off points differ between agencies but are nonetheless very similar and do not exceed 0.1mg/m3.